Organizations : behavior, structure, processes - Gibson, James L.; Ivancevich, John M.; Donnelly, James H. (Dallas : Business Publications, 1979)
An organization or organisation is an entity comprising multiple people, such as an institution or an association, that has a collective goal and is linked to an external environment. The word is derived from the Greek word organon, which means "organ".
Includes bibliographical references and index.
aia 05/07/2017
Loans
Keywords: Organizational sociology; Organizational behavior; Leadership; Organizational effectiveness